SYNTHESIS 7-HYDROXY-3’,4’-DIMETHOXYISOFLAVON FROM EUGENOL - Andi Hairil Alimuddin; Muhammad Idham Darussalam Mardjan; Sabirin Matsjeh; Chairil Anwar; Mustofa Mustofa; Eti Nurwening Sholikhah (Indonesian Journal of Chemistry, 2011)
Eugenol from the isolation of clove leaves oil had been utilized in the synthesis of 7-hydroxy-3',4'-dimethoxy-isoflavone based on deoxybenzoin intermediate. The raw material was firstly converted into methyleugenol using DMS (89.87%). Secondly, methyl eugenol was oxidized using KMnO4 to produce 3,4-dimethoxybenzyl carboxylic acid (21%). Friedel-Craft acylation of it with recorcinol produced 3,4-dimethoxybenzyl-2',4'-dihydroxyphenyl ketone (deoxybenzoin intermediate) in 78% yield. Eventually, cyclization of the intermediate with reagents of BF3.OEt2/DMF/POCl3 yielded 7-hydroxy-3',4'-isoflavone in 85% yield.